Modulator therapies for cystic fibrosis. Issue 4 (April 2019) - Haq, Iram J.; Parameswaran, Meena Chow; Abidin, Noreen Zainal; Socas, Attaybenes; Gonzalez-Ciscar, Andrea; Gardner, Aaron I; Brodlie, Malcolm
Abstract: Cystic fibrosis (CF) is a life-limiting genetic disease that arises from defects in the cystic fibrosis transmembrane conductance regulator (CFTR) gene and protein. This causes abnormal epithelial ion transport. CF is a multisystem condition but airway infection and inflammation carry the greatest treatment burden and are the predominant cause of morbidity and mortality. Novel therapeutic strategies have recently been developed to target specific molecular defects arising from CFTR mutations. These CFTR modulator therapies are designed to correct the underlying protein processing defect or to potentiate CFTR function to improve ion transport. Such advances have revolutionized CF treatment approaches, which have previously only addressed downstream effects, and hold significant promise for the future. This review will summarize recent advances in CFTR modulator development and how these have impacted upon treatment outcomes and the lives of people with CF.